Task Demands in OSCEs Influence Learning Strategies. Issue 3 (3rd July 2017) - Lafleur, Alexandre; Laflamme, Jonathan; Leppink, Jimmie; Côté, Luc
ABSTRACT: Theory : Models on pre-assessment learning effects confirmed that task demands stand out among the factors assessors can modify in an assessment to influence learning. However, little is known about which tasks in objective structured clinical examinations (OSCEs) improve students' cognitive and metacognitive processes. Research is needed to support OSCE designs that benefit students' metacognitive strategies when they are studying, reinforcing a hypothesis-driven approach. With that intent, hypothesis-driven physical examination (HDPE) assessments ask students to elicit and interpret findings of the physical exam to reach a diagnosis ("Examine this patient with a painful shoulder to reach a diagnosis"). Hypotheses : When studying for HDPE, students will dedicate more time to hypothesis-driven discussions and practice than when studying for a part-task OSCE ("Perform the shoulder exam"). It is expected that the whole-task nature of HDPE will lead to a hypothesis-oriented use of the learning resources, a frequent use of adjustment strategies, and persistence with learning. Method : In a mixed-methods study, 40 medical students were randomly paired and filmed while studying together for two hypothetical OSCE stations. Each 25-min study period began with video cues asking to study for either a part-task OSCE or an HDPE. In a crossover design, sequences were randomized for OSCEs and contents (shoulder or spine). Time-on-task for discussions or practice were categorized as "hypothesis-driven" or "sequence of signs and maneuvers." Content analysis of focus group interviews summarized students' perception of learning resources, adjustment strategies, and persistence with learning. Results : When studying for HDPE, students allocate significantly more time for hypothesis-driven discussions and practice. Students use resources contrasting diagnoses and report persistence with learning. When studying for part-task OSCEs, time-on-task is reversed, spent on rehearsing a sequence of signs and maneuvers. Conclusions : OSCEs with similar contents but different task demands lead to opposite learning strategies regarding how students manage their study time. Measuring pre-assessment effects from a metacognitive perspective provides empirical evidence to redesign assessments for learning.